Creating happy relationships a guide to partner skills - Nelson-Jones, Richard; Sage eBooks (London : Cassell, 1999)
This is a practical guide to the skills necessary for developing and maintaining successful partner relationships, presenting a positive emphasis on creating happiness for yourself or others. Practical exercises are included.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Couples; Interpersonal communication; Electronic books